Dysregulated Erythroid Mg2+ Efflux in Type 2 Diabetes - Ferreira, Ana; Rivera, Alicia; Wohlgemuth, Jay G.; Dlott, Jeffrey S.; Snyder, L. Michael; Alper, Seth L.; Romero, Jose R. (Frontiers in Cell and Developmental Biology, 2022)
Hyperglycemia is associated with decreased Mg2+ content in red blood cells (RBC), but mechanisms remain unclear. We characterized the regulation of Mg2+ efflux by glucose in ex vivo human RBC. We observed that HbA1C values correlated with Na+-dependent Mg2+ efflux (Na+/Mg2+ exchange) and inversely correlated with cellular Mg content. Treatment of cells with 50 mM D-glucose, but not with sorbitol, lowered total cellular Mg (2.2±0.1 to 2.0±0.1 mM, p<0.01) and enhanced Na+/Mg2+ exchange activity (0.60±0.09 to 1.12±0.09 mmol/1013 cell x h [flux units, FU], p<0.05). In contrast, incubation with the selective Src family kinase inhibitors PP2 or SU6656 reduced glucose-stimulated exchange activation (p<0.01). Na+/Mg2+ exchange activity was also higher in RBC from individuals with type 2 diabetes (T2D, 1.19±0.13 FU) than from non-diabetic individuals (0.58±0.05 FU, p<0.01). Increased Na+/Mg2+ exchange activity in RBC from T2D subjects was associated with lower intracellular Mg content. Similarly increased exchange activity was evident in RBC from the diabetic db/db mouse model as compared to its non-diabetic control (p<0.03). Extracellular exposure of intact RBC from T2D subjects to recombinant peptidyl-N-glycosidase F (PNGase F) reduced Na+/Mg2+ exchange activity from 0.98±0.14 to 0.59±0.13 FU (p<0.05) and increased baseline intracellular Mg content (1.8±0.1 mM) to normal values (2.1±0.1 mM, p<0.05). These data suggest that the reduced RBC Mg content of T2D RBC reflects enhanced RBC Na+/Mg2+ exchange subject to regulation by Src family kinases and by the N-glycosylation state of one or more membrane proteins. The data extend our understanding of dysregulated RBC Mg2+ homeostasis in T2D.